Audacity of the spirit - Losev, A. F. (Value Inquiry Book Series, 2019)
Audacity of the Spirit by A.F. Losev (1893-1988) dares us to think holistically, dialectically. Translated from the Russian original Дерзание духа (Politizdat Moskva, 1988) by Peter R. Weisensel and Vitali I. Betaneli, the book falls into three parts: the dialectical method; Losev's application of dialectics to history and culture; and his personal reflections on studying philosophy. Losev's insatiable intellectual curiosity probes a remarkable variety of areas. Positions he considers, though, are not always easily reconcilable, as with Marxism-Leninism and Orthodox Christianity. In Losev's conception of culture, however, culture and the intrinsic unity of any given cultural order is the common element that underlies everything living, even the order's incompatibles. The given culture cannot be reduced to any single position nor to all of them taken together. Audacity of the Spirit is an introduction to dialectics for beginners, but it is also a major philosopher's summing-up of his reflections to a non-specialized audience.